Contribution of the Energy Management System (ISO 50001) to ESG - Poltronieri, C. F. [UNESP]; Espuny, M. [UNESP]; Xavier, Y. S.M. [UNESP]; Hernandez-Vivanco, A.; Bernardo, M.; Oliveira, O. J. [UNESP] (My University, 2024)
Purpose - Given the importance of efficient energy management and sustainability, this article seeks to identify relationship of the ISO 50001 with sustainability, using the Environmental, Social and Governance (ESG) criteria for this purpose. Design/methodology/approach - The methodological procedure adopted has been qualitative and consisted in document analysis and the creation of a relationship matrix. Based on that, it was possible to assess at which level each of the sub-clauses of ISO 50001 contributes to achieving ESG elements, considering the Morgan Stanley Capital International (MSCI) criteria. A team of five academics analyzed individually the standard and classified all sub-clauses according to the criteria. Then, based on the individual means and ranges, a second analysis was conducted to assess the points where there was the greatest difference of opinion between the evaluations. Findings - Among all aspects evaluated, those regarding Product liability, a part of the Social aspect of ESG, sparked the most disparity among researchers. In essence, experts found ambiguity in ISO 50001 concerning its contribution to “Product liability”; some perceived a significant contribution, while others saw none directly, suggesting only indirect influence even after reassessment. Conversely, Social opportunities within the Social aspect provoked the least uncertainty. Consensus swiftly emerged that ISO 50001 requirements offer limited direct contribution to ESG elements. Originality/value – This study assesses the ISO 50001 standard's contribution to ESG, considering that both are relevant subjects and usually treated separately.
Keywords: Environmental; Governance; ISO 50001; Social